Interview with Prof. Dr. Paula Kalaja - Kalaja, Paula; Melo-Pfeifer, Sílvia; Ruano, Bruna Pupatto; del Olmo, Francisco Calvo; Friedrich, Tatyana Sheila (Revista X, 2021)
Paula Kalaja, Professor Emerita (University of Jyväskylä, Finland), is one of the pioneers in the use of visual methods in Applied Language Studies, having inspired a range of graduates, post-graduates, and researchers around the world. Her research interests crisscross the use of visual methods, beliefs about languages, language teaching and language learning, and identity, with astonishing creativity and a visionary sense of research. The editors of the special issue “Visual methods in the research with plurilingual audiences: multidisciplinary perspectives” talked to her about how she sees the past, present and future of visual methods in research and teaching, across disciplinary fields, and during and beyond the COVID-19 pandemic.